1992
DOI: 10.1680/geot.1992.42.2.303
|View full text |Cite
|
Sign up to set email alerts
|

characterization of the Bothkennaar clay: an overview

Abstract: Following the purchase by the Science and Engineering Research Council of a soft clay test site at Bothkennar in Scotland, work has been carried out to provide data characterizing the clay for the benefit of future research projects. State of the art methods were used to enhance the research value of the characterization project. Fieldwork in 1989 involved high quality sampling using equipment from Lava] and Sherbrooke Universities in Canada, and a 100 mm fixed piston sampler operated by the Building Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(46 citation statements)
references
References 12 publications
3
43
0
Order By: Relevance
“…14. As there are several approaches to estimating s, from the SBP, the original site data were accessed and fitted with computer-aided modelling to check the reported strengths using full expansion-contraction analysis; similar values of s, to those reported by Hight et al (1992) were found. As can be seen, the SBP strengths, uncorrected for any L/D bias, lie inside the uncertainty of the triaxial data, although with a slightly different trend against depth.…”
Section: II -Cho 2 + M ~ = 3 (1 + Ln[i(l -A"+')]} (4) %mentioning
confidence: 74%
See 1 more Smart Citation
“…14. As there are several approaches to estimating s, from the SBP, the original site data were accessed and fitted with computer-aided modelling to check the reported strengths using full expansion-contraction analysis; similar values of s, to those reported by Hight et al (1992) were found. As can be seen, the SBP strengths, uncorrected for any L/D bias, lie inside the uncertainty of the triaxial data, although with a slightly different trend against depth.…”
Section: II -Cho 2 + M ~ = 3 (1 + Ln[i(l -A"+')]} (4) %mentioning
confidence: 74%
“…In conclusion, there must be a systematic bias kennar from seismic shear wave measurements in s, derived from the SBP using cylindrical (Hight et al, 1992). This modulus profile comcavity theory because of finite pressuremeter bines with the uncorrected SBP s, profile to give length, and the authors' suggestion of a rigidityrigidities of about I, = 650.…”
Section: II -Cho 2 + M ~ = 3 (1 + Ln[i(l -A"+')]} (4) %mentioning
confidence: 84%
“…It has been widely reported that for geomaterials there is an Sshape relationship between the shear modulus G and the shear strain ª (Hight et al, 1992;Iwasaki et al, 1978). The experimental data on the variation of shear modulus with shear strain from Iwasaki et al (1978) are shown in Figure 5 by points.…”
Section: Shear Moduli Of Geomaterialsmentioning
confidence: 97%
“…Hight et al 9 identified three principal units at Bothkennar, namely the bedded, mottled and laminated facies.…”
Section: Work At the Uk's Science And Engineering Research Council (Nmentioning
confidence: 99%
“…Hight et al 9 and Paul et al 11 summarise the depositional environment as being in relatively sheltered and, therefore, quiet, saline or brackish water, between 7 m and 20 m deep. A local more energetic environment, perhaps associated with a subtidal channel in water depths of a few metres, would have been associated with the laminated facies.…”
Section: Work At the Uk's Science And Engineering Research Council (Nmentioning
confidence: 99%